PERLINDUNGAN PENGGUNA GAS BUMI ATAS KEBOCORAN PIPA PENYALUR MILIK PT PERUSAHAAN GAS NEGARA (PERSERO) TBK - Lestari, Sartika Nanda; Diandra, Nikita (Fakultas Hukum, Universitas Diponegoro, 2019)
ABSTRACT The use of natural gas energy is emphasized by the government, in order to decrease the amount of fuel subsidy that giving impact in increasing energy and economic security. The household sector is the highest natural gas consumer, because it is cheaper and cleaner than gasoline and produces less greenhouse emissions than its counterparts. But in practice, the safety of the pipeline is not fully met. Gas leak is one of the the example which caused damage on the consumer. This study will examine the implementation of PT. PGN Tbk gas pipeline system and the consumer protection on gas leak using socio legal research. The results showed that PT. PGN Tbk as natural gas distributor business operators responsible if a leak occurs in the distribution pipeline in the form of repairs and compensation Keywords: Natural Gas, Leaking Pipes, Consumer Protection, Responsibility of Service Providers.